Analisis Pengaruh Kualitas Sistem Informasi E-Commerce Terhadap Kepuasan Pengguna Dan Loyalitas Pelanggan (Studi Kasus Pada Platform Marketplace X) - Antika Ayu Moncha; Ayu Septiyani; Dina Nadifa (Journal of Science, Technology, and Innovation, 2025)
This study aims to analyze the influence of e-commerce information system quality on user satisfaction and customer loyalty, with user satisfaction positioned as a mediating variable. The research adopts a Systematic Literature Review approach by examining peer-reviewed journals in the fields of information systems, e-commerce, and digital marketing. The findings indicate that information system quality, including system reliability, ease of use, security, and information accuracy, has a significant effect on user satisfaction. User satisfaction plays a crucial role in translating system quality into long-term customer loyalty, as loyal behavior emerges from consistent and positive user experiences rather than technical performance alone. The results also reveal that satisfaction strengthens trust, engagement, and repurchase intentions among e-commerce users. This study contributes to the literature by providing a comprehensive understanding of the mediating role of user satisfaction in the relationship between information system quality and customer loyalty. Practically, the findings suggest that e-commerce platforms should prioritize user-centered system development to enhance satisfaction and sustain customer loyalty in a highly competitive digital marketplace.